Phosphoproteomics Reveals Regulation of Secondary Metabolites in Mahonia bealei Exposed to Ultraviolet-B Radiation - Liu, Amin; Liu, Shengzhi; Li, Yaohan; Tao, Minglei; Han, Haote; Zhong, Zhuoheng; Zhu, Wei; Tian, Jingkui (Frontiers in Plant Science, 2022)
Mahonia bealei (M. bealei) is a traditional Chinese medicine containing a high alkaloid content used to treat various diseases. Generally, only dried root and stem are used as medicines, considering that the alkaloid content in M. bealei leaves is lower than in the stems and roots. Some previous research found that alkaloid and flavonoid contents in the M. bealei leaves may increase when exposed to ultraviolet B (UV-B) radiation. However, the underlying mechanism of action is still unclear. In this study, we used titanium dioxide material enrichment and mass-based label-free quantitative proteomics techniques to explore the effect and mechanism of M. bealei leaves when exposed to UV-B treatment. Our data suggest that UV-B radiation increases the ATP content, photosynthetic pigment content, and some enzymatic/nonenzymatic indicators in the leaves of M. bealei. Moreover, phosphoproteomics suggests phosphoproteins related to mitogen-activated protein kinase (MAPK) signal transduction and the plant hormone brassinosteroid signaling pathway as well as phosphoproteins related to photosynthesis, glycolysis, the tricarboxylic acid cycle, and the amino acid synthesis/metabolism pathway are all affected by UV-B radiation. These results suggest that the UV-B radiation activates the oxidative stress response, MAPK signal transduction pathway, and photosynthetic energy metabolism pathway, which may lead to the accumulation of secondary metabolites in M. bealei leaves.